Cost over Use? Analysing the Cost-Effectiveness of E-Book Acquisitions at the University of Colombo Library - Johoran, S. Shabnam (Sri Lanka Library Association, 2026)
Academic libraries worldwide are increasingly prioritising the purchase of e-books, raising questions about their cost-effectiveness and actual usage. This study examines the efficiency of e-book acquisition at an academic library in Sri Lanka and evaluates whether the investment has yielded greater value. The objectives of the present study were to examine trends and patterns in e-book usage, to assess expenditure on e-book acquisitions across various subject areas, to evaluate the cost-effectiveness of e-book acquisitions in different disciplines, and to identify key challenges and constraints in the acquisition and management of e-books. To achieve these objectives, a quantitative, descriptive research design was employed. Usage statistics of e-books were obtained from publishers. The details on e-book procurement and expenditure were obtained from the acquisitions division of the library. According to the study, e-book usage has been declining over the years, while the cost per use has been steadily rising. Limited information technology infrastructure, inadequate budget, and low user awareness of the resources available were identified as primary challenges in establishing an e-book collection. The results suggest that e-book purchases should be more focused, concentrating on subject areas that are in greater demand, particularly social sciences, management, medicine, and education. Furthermore, the study recommends holding user awareness sessions on e-books. This research may help academic libraries in making informed decisions about future investments in e-books and collection development by providing evidence-based insights on usage patterns, costs, and acquisition challenges.
Keywords: Academic library; Cost-effectiveness; E-book usage; Library acquisitions; Sri Lanka